Alleviation of sodic water irrigation induced sodicity through microbial bioformulations - MEENA, HARI MOHAN; MAVI, M S; SAINI, TANIYA; CHOUDHARY, O P; ARORA, SANJAY (The Indian Journal of Agricultural Sciences, 2025)
A field experiment was conducted during rainy (kharif) season of 2019, 2020 and 2021 at Punjab Agricultural University, Ludhiana, Punjab to evaluate the potential of microbial bio-formulations with or without gypsum for ameliorating irrigation water-induced sodicity stress. The experiment was laid out in a split plot design (SPD) with irrigation water quality and gypsum application as the main treatment and microbial bio-formulation inoculation as the sub treatment with three replications. The soil was irrigated with canal water (CW) and sodic water (SW) (RSC 12.5 meq/L) while gypsum was applied at three rates, viz. 12.5%, 25% and 50% of gypsum requirement (GR) under SW. Cotton seeds were inoculated just before sowing with microbial consortia, viz. (a) un-inoculated; (b) Azo (Azotobacter); (c) Azo + PSB (phosphorous solubilizing bacteria) and (d) Azo + PSB + ZnSB (Zinc solubilizing bacteria). Results revealed that compared with CW irrigated plots, seed-cotton yield decreased by 27.4% in SW irrigated plots. Likewise, soil pH values increased by 8.0% while microbial biomass carbon (MBC) decreased by 19.0% under SW compared with CW irrigation. Among different bioformulations, the pooled mean value of seed cotton yield (SCY) was the maximum (45.9 q/ha) for plots inoculated with consortia of Azo + PSB + ZnSB relative to the un-inoculated treatment (41.8 q/ha). Application of microbial consortia Azo + PSB + ZnSB with gypsum (12.5% or 25% of GR) to SW-irrigated plots showed seed-cotton yield greater than those plots amended with gypsum at 50% GR. Similarly, soil pH and exchangeable sodium percentage decreased, whereas MBC and dehydrogenase- activity increased with combined application of gypsum and bioformulations. Therefore, it can be concluded that the farmers facing scarcity of good quality gypsum can use these bio-formulation to substitute some part of the gypsum requirement for ameliorating soils irrigated with SW.